Audit of the impact of the York faecal calprotectin care pathway on colonoscopy activity. Issue 4 (24th October 2019) - Turvill, James; Turnock, Daniel
Abstract : Background: The York faecal calprotectin care pathway (YFCCP) was developed to optimise effective primary care differentiation between irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD). We undertook an audit of colonoscopy activity at York Teaching Hospitals after the introduction of the YFCCP, to assess its impact. Methods: Faecal calprotectin (FC) results were reconciled with colonoscopy activity in patients 18–60 years after the implementation of the YFCCP. This permitted individual patient tracking of their FC values, the timing of those requests by primary care, the date of subsequent referral and investigation and the end clinical diagnoses. Results: Primary care uptake of FC increased fourfold with the introduction of the YFCCP. Following implementation, FC-related referrals for colonoscopy fell from 24% to 13%. The number of patients needed to colonoscope to diagnose organic colonic disease (IBD, significant adenomatous polyps or colorectal cancer) fell from 6.8 to 3.8 when the YFCCP was applied. This represents a cost saving of £41 015 per thousand patients tested in primary care. We estimate that outpatient time to diagnosis fell from a median of 41 to 29 days. Conclusion: This audit of FC activity and colonoscopy outcomes provides substantial supportive evidence for the effectiveness of the YFCCP. Popular in primary care, it has led to a reduction in referrals. The diagnostic accuracy determined in this audit is in line with earlier evaluations. Accepting the weaknesses of audit we conclude that this evaluation likely underestimates the benefits of the YFCCP in terms of resource use saving and time to diagnosis.